FORMULATION AND OPTIMIZING OF A ANTI-AGING COSMETIC CREAM - JUNCAN, A. M.; LUNG, C. (Studia Universitatis Babeș-Bolyai Physica, 2016)
The research and development of cosmetics, especially the composite active ingredients, should be based on their clarified sources, structures, interactive mechanisms with the skin, and, most importantly, their efficacy and safety on the targeted components of skin. This study has as main objective the development and formulation of a anti-aging cosmetic product which incorporates effective and innovative ingredients, used in the developed formulation to support the cosmetic claimed of the product. An important study is the quality control of the anti-aging cream by determining the physico-chemical characteristics and appropriate pharmacotechnical (pH, viscosity) characteristics, both initially and over time (30 days from the preparation of the product). The formulation is monitored under accelerated stability studies over a period of 30 days while maintaining the product at 4, 20 and 40 °C.